Same syllabus, different country – using DREEM to compare the educational environments at two Pharmacy schools - Wong, Pei Nee; John, Dai N; Deslandes, Rhian E; Hughes, M. Louise (Pharmacy Education, 2015)
Background: A new pharmacy twining programme between universities in Malaysia (Taylor’s, TU) and the United Kingdom (Cardiff, CU) started in 2011. Aims: To compare the pharmacy students’ perceived educational environments in two institutions using the same syllabus. Methods: In October 2012, a modified version of DREEM (Dundee Ready Education Environment Measure) was administered to Year 2 and Year 3 students in both schools, relating views to the previous academic year. Results: For both schools, the total mean scores revealed a positive education environment. CU students perceived the environment to be significantly more positive than TU students (145/200 vs 128/200, p<0.005). Sub-domain scores showed significant difference between TU and CU (t-test, p<0.05). Highest scores of perceptions of the learning environment in TU were associated with learning and lowest with atmosphere. Conclusion: The study has provided useful information about the strengths and areas of improvement for both schools. Plans are being employed to further enhance the quality of the educational environment.